Expansão e potencialização da compreensão da realidade via jornalismo literário: empatia, reflexão e aproximação nas narrativas não-ficcionais das jornalistas-escritoras Daniela Arbex, Eliane Brum e Consuelo Dieguez - Oliveira, Camila Tapia Passos de (2022)
Considering the conception of a humanized, polyphonic journalism free from the standardization of perishable and automatic reproduction writing, this research dwells on the hybrid narratives of Literary Journalism to understand how the use of elements of literature in journalistic productions fosters an expansion and an enhancement of the understanding of social reality and contributes to the construction and maintenance of collective memory of societies. Structured with a qualitative theoretical-methodological approach, this is a bibliographic research with an empirical part, in which are analyzed, through Discourse Analysis and Narratives Analysis, works by three Brazilian authors representative of this narrative model: Todo Dia a Mesma Noite, by Daniela Arbex (2018a); A Vida que Ninguém Vê, by Eliane Brum (2006); and Bilhões e Lágrimas, by Consuelo Dieguez (2014). Stem from the respective categories of analysis empathy, reflection, and approximation, originating from broader discursive widgets, it is shown which are and in which way the literary elements identified in the books-report of these journalist-writers are utilized. Such features, with all their subjective power, are revealed as precious for journalistic works that propose to be distinctive. Therefore, there is a contribution to the debates on Literary Journalism in Brazil and the many ways to use it in favor of productions with greater deepening, durability, aesthetic refinement, and reach.